1983
DOI: 10.1111/j.0022-3646.1983.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOMETRY OF BATRACHOSPERMUM POPULATIONS INTERMEDIATE BETWEEN B. BORYANUM AND B. ECTOCARPUM (RHODOPHYTA)1

Abstract: Batrachospermum plants collected as part of a comprehensive study of New England streams were found to be intermediate between B. boryanum Sirdt. find B. ectocarpum Sirdt. Sixty‐four specimens from ten Rhode Island streams were examined for several characteristics in replicates of two to four hundred. The size ranges obtained were then compared with previous published data for B. boryanum and B. ectocarpum from Europe, Asia and North America. The Rhode Inland populations and individuals exhibited as much or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…Mori (1975) developed a new set of criteria to distinguish the infrageneric taxa of the B. gelatinosum group, but most characters, for example the shape of the carposporophyte-bearing branch cells, are not taxonomically useful. Sheath & Burkholder (1983) found that the I number of fascicles per pericentral cell could vary from 3 to 7 on the same specimen and, therefore, this character cannot be applied to distinguish taxa. The validity of carposporophyte position as a taxonomic criterion was investigated in this study.…”
Section: (9-12)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mori (1975) developed a new set of criteria to distinguish the infrageneric taxa of the B. gelatinosum group, but most characters, for example the shape of the carposporophyte-bearing branch cells, are not taxonomically useful. Sheath & Burkholder (1983) found that the I number of fascicles per pericentral cell could vary from 3 to 7 on the same specimen and, therefore, this character cannot be applied to distinguish taxa. The validity of carposporophyte position as a taxonomic criterion was investigated in this study.…”
Section: (9-12)mentioning
confidence: 99%
“…Batrachospermum (= Moniliformia Sirodot, 1873) of the freshwater red algal genus BatrachOspermum is generally characterised by the following features: welldeveloped whorls, undifferentiated and straight carpogonial branches arising from both fascicle and pericentral cells, carpogonia with club-to urn-shaped trichogynes, and small, globose, pedicellate carposporophytes at various distances from the whorl axis (Mori, 1975;Starmach, 1977;Kumano, 1993). Sheath & Burkholder (1983) suggested merging sections Batrachospermum and Helminthoidea Sirodot ex De Toni (1897) since they found the two features previously used to separate these sections, trichogyne shape and involucral filament length, to be quite variable. Necchi & Entwisle (1990) agreed with this conclusion, but recently Kumano (1993) chose to keep the two sections separate on the basis of length of involucral filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of a dioecious species is advantageous because the effects of flow on fertilization rates can be determined without self fertilization being a factor. This species is also appropriate for investigation because it is widespread in North America, Europe and Asia (summarized by Sheath & Burkholder, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Only 17 of these populations examined were mature, having carposporophytes. A distinct attribute observed in all the North American populations is curled branch tips (Figs 13, 16), previously noted by Sheath & Burkholder (1983). This characteristic was not reported in the type specimen (Vis et al, 1995).…”
Section: Resultsmentioning
confidence: 52%
“…1). (Hylander, 1928;Drouet, 1933;Croasdale, i935;Britton, I944;Flint, 1948Flint, , 1949Flint, , 1957aPrescott, 1962;Whifford & Schumacher, 1968, 1973Woelkerling, 1975;Sheath & Burkholder, 1983, 1985Sheath & Cole, 1993). Additional herbarium specimens from locations in California, Indiana, Nevada, New Brunswick, New Jersey, South Carolina, South Dakota, Washington and Wyoming extend the confirmed range of this species (see Appendix).…”
Section: Resultsmentioning
confidence: 86%